Socio-Economic Health Status of Elderly in Kerala (Online International Interdisciplinary Research Journal, 2016)
Of all the states, Kerala is reported to have the highest proportion of the elderly in India. As per 2001 census the aged comes to 10.5 percent of the total population of the state. From the review of the literature, it is found that studies relating to the elderly staying in old age homes are very rare. The only study which has thrown some light on this is the article by IrudayaRajan (2000). But studies which have attempted to compare the health status as well as determinants of health status of the elderly staying in old age homes and those staying with family members have not been carried out by anyone, in the context of Kerala. The study found that socio economic variables which have exert influence on the health status of elderly in Kerala and the health status of old age home inmates is worse than that of elderly persons staying with family.